Ukraine in histories and stories essays by Ukrainian intellectuels - Jermolenko, Volodymyr Anatolijovyč 1980-
This fascinating collection of texts by contemporary Ukrainian writers, historians, philosophers, political analysts, and opinion leaders combines reflections on Ukraine's history-or histories-and analyses of the present as well as conceptual ideas and life stories. The authors present a multi-faceted image of Ukrainian memory and reality: from the Holodomor to Maidan, from Russian aggression to cultural diversity, from the depth of the past to the complexity of the present. Essential reading for anyone interested in Ukraine. The contributors of this book are prominent Ukrainian historians, writers, philosophers, political analysts, and intellectuals. The book was published with support from the Ukrainian Cultural Foundation
Keywords: Ukraine; History; intellectual history; Contemporary Life; Essays; Zeitgeschichte